2020
DOI: 10.1101/2020.03.30.016535
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Small molecule inhibition of human cGAS reduces total cGAMP output and cytokine expression in cells

Abstract: ABSTRACTThe cGAS-STING pathway is a major mechanism that mammalian cells utilize to detect cytoplasmic dsDNA from incoming viruses, bacteria, or self. CYCLIC GMP-AMP SYNTHASE (cGAS) is the sensor protein that directly binds dsDNAs. cGAS synthesizes cyclic GMP-AMP (cGAMP), which binds to the adaptor STIMULATOR OF INTERFERON GENES (STING), activating an INTERFERON REGULATORY FACTOR 3 (IRF3)-mediated immune response. Constitutive activation can result in interferonopathies such as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…al., we observe HIV-1 infection induces cGAS signaling in a NONO-dependent manner in MDDCs (Figures 4A and S4A). However, we find that NONO depletion in THP-1 cells, which maintain an intact innate response to HIV (Collins et al, 2015; Gao et al, 2013; Sumner et al, 2020; Sun et al, 2013; Wiser et al, 2020; Yoh et al, 2015), has no significant effect on innate immune response to HIV-1(with Vpx), as well as HIV-2, infection (Figures 4B). In attempt to determine whether NONO participates in the initial recognition of incoming virus particles in MDDCs, we evaluated the frequency of NONO association with incoming HIV-1 virions.…”
Section: Resultsmentioning
confidence: 88%
“…al., we observe HIV-1 infection induces cGAS signaling in a NONO-dependent manner in MDDCs (Figures 4A and S4A). However, we find that NONO depletion in THP-1 cells, which maintain an intact innate response to HIV (Collins et al, 2015; Gao et al, 2013; Sumner et al, 2020; Sun et al, 2013; Wiser et al, 2020; Yoh et al, 2015), has no significant effect on innate immune response to HIV-1(with Vpx), as well as HIV-2, infection (Figures 4B). In attempt to determine whether NONO participates in the initial recognition of incoming virus particles in MDDCs, we evaluated the frequency of NONO association with incoming HIV-1 virions.…”
Section: Resultsmentioning
confidence: 88%
“…The role of cGAS in the immunostimulatory activity of the compounds was investigated in the RAW-Dual reporter cells by pretreating the cells with a dose response of the established small molecule inhibitor of cGAS, RU.521 (33,61,62) (Figure 2G). Four hours after incubation with RU.521, the cells were treated with the EC75 concentration of 95-BP/D-PDB (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Later studies showed that docking of Ru.521 into the active site of human cGAS (Zhou et al, 2018) is suboptimal and the compound therefore has reduced activity against recombinant human cGAS (Lama et al, 2019). Recently, a study found comparable activity of Ru.521 against both mouse and human cGAS in cellular assays (Wiser et al, 2020). X-ray crystal structures of cGAS in complex with Ru.521 have been solved (mouse cGAS: PDB 5XZG; human cGAS: PDB 6O47).…”
Section: Discussionmentioning
confidence: 99%